Efforts to Manage the Hidden Heaven of the World in Pamah Semelir Langkat-North Sumatra - Mavianti; Harun, Makmur; Putri, Ririn Ananda; Agustin, Wita Sania; Andreani, Putri (Indonesian Journal of Community Services Cel, 2022)
This paper aims to reveal the hidden beauty of the tourist village of Pamah Semelir which is located in the village of Telagah, Sei Bingai District, Langkat Regency, North Sumatra Province. This village holds a lot of natural beauty that amazes the eyes and soothes the heart. This location has many tours that can be visited by local tourists and tourists from outside, cold tourist attractions with beautiful views will add to the attraction of tourists to take a break from the hustle and bustle of the city. Pamah breezy is also often used as a camping place by young people and this place is also one of the choices for residents who visit Langkat district because the nature is still beautiful and still awake even though when in the location of pamah semelir the signal is lost but does not reduce interest in enjoying the beauty nature. However, problems arise due to the pandemic so that this tourist location does not get treatment so that it has an impact on less than optimal care. Therefore, according to the author, several things need to be done, namely 1) The need for guidance in terms of managing halal and good food in the context of services for visiting tourists to make it more comfortable in choosing food, 2) The need for assistance in determining the price of food being traded so that it does not there is too much variation with non-tourist areas, in this case also in order to attract tourists to this area, and 3) There are inadequate facilities that support the availability of public vehicles. In this case, local government support is needed to provide services for tourists who do not have private vehicles.